Making Sense of Ideological Preferences: A Moral Foundations Theory Approach - Mahajan, Aarushi (My University, 2024)
Beliefs, attitudes, values, perceptions, and moral judgements are crucial to understanding individual preferences, goals, and decisions. It becomes necessary for both governments and business organizations to comprehend personal disposition of its citizens and employees, respectively in order to roll out important policy decisions and smoothly tackle unforeseen incidents. The study critically examines the extant research that draws upon Moral Foundations Theory (MFT) as a theoretical lens to understand and examine attitudes, beliefs, intentions, decisions, ideological preferences, and issue positions. Consequently, it was observed that MFT has been applied to understand religious orientation, political ideology, specific attitudes (e.g., attitude towards stem cell research, consumer attitudes towards gray market products), culture-war issues, and party preferences. By employing MFT, this study aims to examine the differences in moral endorsements across the liberal-conservative political spectrum. Additionally, the study intends to investigate the capacity of moral foundations in explaining a varied set of economic attitudes thereby, contributing to an underexplored application of MFT. In this context, the study plans to examine the extent to which moral foundations explain lay attitudes towards government role in social welfare, attitudes towards economic fairness in terms of treatment of workers, and general satisfaction with the economy in terms of distributive status-quo. Furthermore, the study aims to examine variability in the moral endorsements and the political orientation across religious spectrum. In addition, the mediating role of religiosity in the relationship between moral foundations and political orientation (PO) is assessed. Extant literature suggests that there is scant evidence of the application of aspects of MFT to unveil nuances of decision-making in businesses. However, a central tenet of MFT- moral judgement of right and wrong- is an important predictor of consumer perceptions of products sold through unauthorized channels such as gray markets and counterfeits which pose a huge challenge for brand-sensitive businesses worldwide. In addition, the extant literature employs either empirical or qualitative methodology to investigate various aspects of MFT. Thus, lastly, the study extends the application of MFT to make sense of decision-making in business organizations. To be precise, the study intends to analytically study the role of consumers’ moral judgement and perceptions in influencing strategic firm decisions to tackle unauthorized gray market activity. In this regard, the study considers two important decisions that a brand may face in the presence of gray markets i.e., appropriate structure (centralized or decentralized) and whether to adopt blockchain technology to combat the gray market menace. Results of the empirical study investigating the proposed conceptual model reveal that political conservatives have a positive association with binding moral foundation (BMF), whereas no significant relation was found between political orientation and individualizing moral foundations (IMF). Moreover, IMF is: (a) positively related to attitudes towards the role of government in providing social welfare, (b) negatively related to the belief that workers are being given fair treatment in the economy, and (c) positively related to the attitudes against economic status-quo. Additionally, a positive relationship was observed between (i) BMF and religiosity, and (ii) religiosity and political orientation. Also, religiosity was found to partially mediate the BMF-PO relationship. Furthermore, the study employed analytical game theoretic modelling to extend the role of MFT in firm’s strategic decision-making. Results of the analytical study reveal that when brand reputation loss owing to consumers’ moral judgement of gray market activity is higher, the following results hold true under the domestic gray market setting: (a) both gray market sales and total sales are higher under a decentralized structure; (b) the manufacturer remains worse-off under the decentralized structure even though the supply chain profit is higher, and the following results hold true under the parallel import setting: (d) it is the optimal strategy for brands to invest in blockchain technology in the high-priced market; (e) blockchain implementation increases brand’s global profit despite reduced profit in the low-priced market. The study presents various implications for multiple stakeholders. Firstly, it becomes necessary for public policymakers and organizational leaders to take into account moral and ideological profile of citizens and employees respectively, while framing new policies. Secondly, managers can strive for satisfactory hiring for the organization by inducting employees who possess moral virtues and ideology that are in sync with the requirements of the primary line of operations in the organization. The analytical study also entails several practical implications for organizations. Companies that face larger reputation loss due to consumers’ moral judgement of gray market indulgence should be extremely careful while using different channel structures. The brands are advised to consider three important aspects before implementing blockchain technology, namely brand equity, consumer profile, and cost of blockchain implementation. When the product diversion or leakage from the authorized channel to the gray market has a severe negative impact on brand equity (brand image) due to moral judgement of gray market activity, then blockchain implementation can be an optimal strategy for brands. The empirical study is limited to student population in the Indian context and employs a cross-sectional design. The limitations of the analytical study involve a deterministic demand model.
Keywords: Ideological Preferences; Moral Foundations Theory; Economic Attitudes; Religiosity; Political Orientation; Gray Markets; Blockchain Technology; Game-theoretic Modelling; Structural Equation Modelling